2019
DOI: 10.31234/osf.io/rkyp3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What factors are most important in finding the best model of a psychological process? Comment on Navarro (2018)

Abstract: Psychology research has become increasingly focused on creating formalized models of psychological processes, which can make exact quantitative predictions about observed data that are the result of some unknown psychological process, allowing a better understanding of how psychological processes may actually operate. However, using models to understand psychological processes comes with an additional challenge: how do we select the best model from a range of potential models that all aim to explain the same p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…We only include the full diffusion comparisons within the main text for ease of communication, as a full diffusion version was found to be the superior model for every participant in every data set. We chose the Bayes factor as it closely aligns with our goal of attempting to find the model that provides the best account of the underlying process (Evans, 2019a, 2019c; Gronau & Wagenmakers, 2019). It should also be noted that many different methods—based on different criteria—exist for selecting between competing theoretical models (Evans, 2019a), such as cross-validation methods that select models based on their ability to predict unseen data (Browne, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…We only include the full diffusion comparisons within the main text for ease of communication, as a full diffusion version was found to be the superior model for every participant in every data set. We chose the Bayes factor as it closely aligns with our goal of attempting to find the model that provides the best account of the underlying process (Evans, 2019a, 2019c; Gronau & Wagenmakers, 2019). It should also be noted that many different methods—based on different criteria—exist for selecting between competing theoretical models (Evans, 2019a), such as cross-validation methods that select models based on their ability to predict unseen data (Browne, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Although this idea is controversial (see Evans, 2019;Gronau & Wagenmakers, 2019, for counter arguments), we note that the argument made by Navarro (2019) calls for greater investment in generalization and extrapolation. Some ideas behind this are discussed in Kennedy and Gelman (2019), but build upon much older ideas (Shavelson, Webb, & Rowley, 1989).…”
Section: Statistical Tools Can't Tell Us What We Want In Practicementioning
confidence: 83%
“…Although we agree that both model evaluation and model comparison are important for understanding psychological processes, we disagree that these two categories should form a continuum for selecting between models. Rather, we argue that these different forms of assessment reflect fundamentally different goals of implementing models that answer fundamentally different questions (see Evans, 2019b, for a more in-depth discussion).…”
Section: Chalk and Cheesementioning
confidence: 98%
“…These assessments are usually made through visual assessments of qualitative trends that can be plotted from the data, which are contrasted to the predictions that the model can make for these aspects of the data. It should be noted that model evaluation contains no correction for model flexibility, and therefore, should not be used to answer confirmatory research questions about which models are superior to others, as these comparisons will be biased towards more flexible models (see Roberts & Pashler, 2000;Evans, 2019b, for more detailed discussions). However, model evaluation is ideal for answering research questions about why certain models are found to be superior to others in model comparison, and what further development may be required to create a better explanation of the underlying process, meaning that it is often used in combination with model development.…”
Section: Introductionmentioning
confidence: 99%